What Is the Role of AI in Social Determinants Analysis? - Rasit Dinc (Rasit Dinc Digital Health & AI Research, 2016)
The social determinants of health (SDoH) are the conditions in which people are born, grow, live, work, and age. These circumstances are shaped by the distri...
Keywords: AI in Public Health; Social; Determinants; Analysis; Artificial Intelligence; Machine Learning; Healthcare